Doubling income of goat farmers through breed improvement - Singh, I; Kumar, M; Singh, G; Kumari, P; Kumari, S; Karel, A; Rohilla, P P (Indian Farming, 2019)
With the aim to improve local goat breed reared by farmers of the adopted villages in (Balarwa, Manai and Binjwariya of Jodhpur) Farmer FIRST Programme, 25 bucks of Sirohi goat breed were purchased in March 2017 from Livestock Research Centre, Bosunda of Rajuvas, Bikaner. These bucks were kept with the flock of 10-15 goats (of the farmers) for breed improvement purpose. The Sirohi buck delivered at farmer’s field through breeding of Sirohi breed gave extra net return of ` 1,350/buck due to extra weight gain with the same feed at one year age. The market preference was also higher for Sirohi buck. Farmers have shown satisfaction towards performance and the progeny of Sirohi bucks due to high income and good adoptability.